2021
DOI: 10.1002/cche.10460
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of wheat cookies’ nutritional quality, by partial substitution with common bean and maize flours, sustained human glycemia and enhanced satiety perception

Abstract: Background As a dietetic source of fiber, protein, vitamins, minerals, and phenolic compounds, common beans have potential benefits in human health, namely in chronic diseases’ prevention (e.g., cardiovascular diseases and colon cancer). Still, legume consumption, especially in European countries, is below recommendations. The consumers demand for innovative, attractive legume‐based food products suggests a potential future increase in consumption of legumes, especially in modern societies, keen on ready‐to‐ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
(47 reference statements)
2
8
0
Order By: Relevance
“…Furthermore, data on the sensorial characteristics of these products provided indications to better identify target consumers as well as to develop bean-based products better adapted to consumer needs. From a nutritional standpoint, the use of composite flours containing common bean flour led, as expected and reported in similar studies [7,12,15,63,64], to products with higher protein and total dietary fiber content and lower amounts of starch and total carbohydrates. Depending on the type of pulse-based snacks (e.g., bars, biscuits, chips, bread, extruded snacks) reported protein concentration has ranged between 8.79% and 29.8%, with extruded snacks having the highest protein content, as they mostly or exclusively contain legume flour [7,64].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, data on the sensorial characteristics of these products provided indications to better identify target consumers as well as to develop bean-based products better adapted to consumer needs. From a nutritional standpoint, the use of composite flours containing common bean flour led, as expected and reported in similar studies [7,12,15,63,64], to products with higher protein and total dietary fiber content and lower amounts of starch and total carbohydrates. Depending on the type of pulse-based snacks (e.g., bars, biscuits, chips, bread, extruded snacks) reported protein concentration has ranged between 8.79% and 29.8%, with extruded snacks having the highest protein content, as they mostly or exclusively contain legume flour [7,64].…”
Section: Discussionsupporting
confidence: 71%
“…Depending on the type of pulse-based snacks (e.g., bars, biscuits, chips, bread, extruded snacks) reported protein concentration has ranged between 8.79% and 29.8%, with extruded snacks having the highest protein content, as they mostly or exclusively contain legume flour [7,64]. The direct comparison between the two types of biscuits produced in the current study with other bean-based biscuits previously described [12,15] showed that the protein content of Biscuit 1 and Biscuit 2 was higher (by on average 11%) than that (ranging between 8% and 10%) reported for biscuits containing bean flour ranging from 12% to 29%, indicating that the composition of the composite flour is also important if other flours beside common bean and wheat are used. In fact, the use of maize flour depleted the protein content of the products [12,15], while the addition of buckwheat flour, together with the presence of eggs, increased it in Biscuit 2 (12% of bean flour) compared to Biscuit 1 (20% bean flour).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, recently some clinical studies have been published in the literature that use only 10 participants for measuring postprandial glycemic response [ 59 , 60 , 61 , 62 ]. Additionally, due to its convenience in application for the participants, a glucometer was used in most of these studies [ 28 , 29 , 30 , 31 , 32 ]. In addition, it was reported that the use of a glucometer for monitoring the postprandial blood glucose level has an acceptable sensitivity [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was a single-blind controlled study. The study consisted of three experimental trials (two test meals and one reference) carried out on three different occasions in accordance with the literature [ 28 , 29 , 30 , 31 , 32 ]. We allowed a one-week wash out period between each visit.…”
Section: Methodsmentioning
confidence: 99%